KAMPANYE PUBLIC RELATIONS #MEDIALAWANCOVID19 DI MEDIA MASSA - Ida Fariastuti; Mukka Pasaribu (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Dozens of Indonesian mass media have united in an educational movement entitled #MediaLawanCovid19. The purpose of this research is to explore how the mass media public relations campaign in Indonesia in the case of Covid 19 (Case Study of the media campaign #MediaLawanCovid19)? The concept used is a public relations campaign, 10 steps campaign planning, the type of campaign, the paradigm in this research is constructivist. The research approach to research is qualitative. The nature or type in this research is descriptive qualitative. The method used is a case study. The data collection technique in this research is in-depth interviews. The validity technique in this research is source triangulation. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The result of this research is that the #medialawancovid19 campaign is a public relations campaign run by a combination of 50 mass media in Indonesia. The #medialawancovid19 campaign is dissected with Anne Gregory's 10 steps, namely: analysis, objectives, public, message, strategy, tactics, time scale, resources, evaluation and review. In addition, the campaign activities carried out by the mass media are a form of social responsibility from media agencies to the current condition of the Indonesian nation in facing Covid 19. Indonesia United against Covid 19 is a big reference for this campaign.